Giá trị của m để hàm số \(y = \frac{1}{3}{x^3} - \left( {m - 1} \right){x^2} + \left( {{m^2} - 3m + 2} \right)x + 5\) đạt cực đ�

Câu hỏi :

Giá trị của m để hàm số \(y = \frac{1}{3}{x^3} - \left( {m - 1} \right){x^2} + \left( {{m^2} - 3m + 2} \right)x + 5\) đạt cực đại tại x = 0?

A. m = 1

B. m = 1 hoặc m = 2

C. m = 6

D. m = 2

* Đáp án

D

* Hướng dẫn giải

\(\begin{array}{l}
y = \frac{1}{3}{x^3} - (m - 1){x^2} + \left( {{m^2} - 3m + 2} \right)x + 5\\
 \Rightarrow y' = {x^2} - 2(m - 1)x + {m^2} - 3m + 1\\
 \Rightarrow y'' = 2x - 2\left( {m - 1} \right).
\end{array}\) 

Hàm số đạt cực đại tại \(x = 0 \Leftrightarrow \left\{ \begin{array}{l}
y'(0) = 0\\
y''(0) < 0
\end{array} \right. \Leftrightarrow \left\{ \begin{array}{l}
{m^2} - 3m + 2 = 0\\
 - 2(m - 1) < 0
\end{array} \right. \Leftrightarrow \left\{ \begin{array}{l}
\left[ \begin{array}{l}
m = 1\\
m = 2
\end{array} \right.\\
m > 1
\end{array} \right. \Leftrightarrow m = 2\) 

Copyright © 2021 HOCTAP247